Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

“I can never be too comfortable”: Race, gender, and emotion at the Hospital Bedside - Cottingham, Marci D.; Johnson, Austin H.; Erickson, Rebecca J. (Qualitative Health Research, 2018)
In this article, we examine how race and gender shape nurses’ emotion practice. Based on audio diaries collected from 48 nurses within two Midwestern hospital systems in the United States, we illustrate the disproportionate emotional labor that emerges among women nurses of color in the white institutional space of American health care. In this environment, women of color experience an emotional double shift as a result of negotiating patient, coworker, and supervisor interactions. In confronting racist encounters, nurses of color in our sample experience additional job-related stress, must perform disproportionate amounts of emotional labor, and experience depleted emotional resources that negatively influence patient care. Methodologically, the study extends prior research by using audio diaries collected from a racially diverse sample to capture emotion as a situationally emergent and complex feature of nursing practice. We also extend research on nursing by tracing both the sources and consequences of unequal emotion practices for nurse well-being and patient care.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; infirmières; intersectionnalité; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; sexisme; systèmes d'oppressions; systèmes hospitaliers; thématiques; travail; travail émotionnel; états-unis

Travail invisible : portraits d'une lutte féministe inachevée - Robert, Camille; Toupin, Louise (Remue-ménage, 2018)
Encore invisible, le travail des femmes? La question peut faire sourciller tant les féministes ont obtenu des gains sur ce front au cours des dernières décennies. Or, si les femmes ont massivement intégré le marché de l'emploi, le travail dit invisible, majoritairement effectué par celles-ci, n'a fait que croître et se complexifier. En plus du strict travail ménager, il se présente sous de multiples visages: la charge mentale de l'organisation familiale, le travail invisible d'intégration des femmes immigrantes, le travail des proches aidantes, celui des aides familiales venues d'ailleurs, des femmes autochtones et racisées, des étudiantes stagiaires, ou encore, des travailleuses du sexe. Comment se décline l'enjeu du travail invisible dans différents milieux, et où en sont les revendications pour faire reconnaître ce travail et le sortir de l'ombre? Rassemblant des militantes féministes et des intellectuelles engagées sur ces questions, cet ouvrage collectif entend remettre le sujet du travail invisible à l'ordre du jour politique tout en proposant des pistes de réflexion et de mobilisation concrètes
Keywords: amériques; approches et analyses; canada; care; cours; fem1300; femmes* autochtones; femmes* immigrantes; inégalités; premier cycle; québec; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail domestique; travail du care; travail du sexe

Prendre en compte les femmes à bas salaires et racisées - Yerochewski, Carole (Nouveaux Cahiers du socialisme, 2018)
Keywords: amériques; approches et analyses; care; cours; discipline; fem1300; inégalités; mouvement syndical; mouvements des femmes*; premier cycle; québec; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail